Efficacy of inhaled hydrogen on neurological outcome following brain ischaemia during post-cardiac arrest care (HYBRID II): a multi-centre, randomised, double-blind, placebo-controlled trial. (April 2023) - Tamura, Tomoyoshi; Suzuki, Masaru; Homma, Koichiro; Sano, Motoaki; ,; Iizuka, Ryoji; Narimiya, Hiromichi; Tsuruta, Ryosuke; Kaneda, Kotaro; Fujita, Motoki; Sasaki, Junichi; Akasaka, Osamu; et al.
Summary: Background: Inhaled molecular hydrogen gas (H2 ) has been shown to improve outcomes in animal models of cardiac arrest (CA). H2 inhalation is safe and feasible in patients after CA. We investigated whether inhaled H2 would improve outcomes after out-of-hospital CA (OHCA). Methods: HYBRID II is a prospective, multicentre, randomised, double-blind, placebo-controlled trial performed at 15 hospitals in Japan, between February 1, 2017, and September 30, 2021. Patients aged 20–80 years with coma following cardiogenic OHCA were randomly assigned (1:1) using blinded gas cylinders to receive supplementary oxygen with 2% H2 or oxygen (control) for 18 h. The primary outcome was the proportion of patients with a 90-day Cerebral Performance Category (CPC) of 1 or 2 assessed in a full-analysis set. Secondary outcomes included the 90-day score on a modified Rankin scale (mRS) and survival. HYBRID II was registered with the University Hospital Medical Information Network (registration number: UMIN000019820) and re-registered with the Japan Registry for Clinical Trials (registration number: jRCTs031180352). Findings: The trial was terminated prematurely because of the restrictions imposed on enrolment during the COVID-19 pandemic. Between February 1, 2017, and September 30, 2021, 429 patients were screened for eligibility, of whom 73 were randomly assigned to H2 (n = 39) or control (n = 34) groups. The primary outcome, i.e., a CPC of 1 or 2 at 90 days, was achieved in 22 (56%) and 13 (39%) patients in the H2 and control groups (relative risk compared with the control group, 0.72; 95% CI, 0.46–1.13; P = 0.15), respectively. Regarding the secondary outcomes, median mRS was 1 (IQR: 0–5) and 5 (1–6) in the H2 and control groups, respectively (P = 0.01). An mRS score of 0 was achieved in 18 (46%) and 7 (21%) patients in the H2 and control groups, respectively (P = 0.03). The 90-day survival rate was 85% (33/39) and 61% (20/33) in the H2 and control groups, respectively (P = 0.02). Interpretation: The increase in participants with good neurological outcomes following post-OHCA H2 inhalation in a selected population of patients was not statistically significant. However, the secondary outcomes suggest that H2 inhalation may increase 90-day survival without neurological deficits. Funding: Taiyo Nippon Sanso Corporation . Translation: For the Japanese translation of the abstract see Supplementary Materials section.